Mediating learning of sound through cultural music and dance stories to Grade 4 farm school learners - Tshitshi, Hlengiwe (Rhodes University, Faculty of Education, Department of Secondary and Post-School Education)
The current South African Natural Science and Technology (NS-Tech) curriculum for grades 4"“9 encourages teachers to integrate Indigenous Knowledge (IK) into their teaching. By doing so, it is hoped that this would contextualise and make science relevant to learners. However, the contradiction is that IK is hardly discussed in the curriculum and there are no clear guidelines on how to integrate it. It is against this background that in this study I used stories about cultural beliefs and practices on traditional music and dance to support Grade 4 NS-Tech from a farm school talking about and making sense of the topic of sound. This study is underpinned by the interpretivist and Indigenous research paradigms. Within the Indigenous research paradigm, I focused on the Ubuntu perspective. A qualitative case study research design was employed, and the study was conducted in the Sarah Baartman District of the Eastern Cape. Four Grade 4 learners and four Indigenous Knowledge Custodians who were all family members were participants in this study. In addition, I invited an NS-Tech teacher to be my critical friend in this study. A focus group interview (sharing circle), participatory and lesson observations and learners' journal reflections were employed to gather data. Vygotsky's sociocultural theory together with Ogunniyi's contiguity argumentative theory were used as lenses to analyse data. A thematic approach to data analysis was employed to come up with sub-themes. Thereafter, common sub-themes were subsequently combined to form themes. The findings of this study revealed that the following factors can significantly enable/constrain the ability of Grade 4 Natural Sciences and Technology learners from a farm school to comprehend and engage with the topic of sound: (1) integration of IK into science lessons, (2) Experiential learning through hands-on activities, (3) Community involvement in knowledge acquisition, and (4) Emotional effect of loud sounds. In addition, the contribution of Indigenous Knowledge Custodians facilitated a notable enhancement in learners' dialogue and understanding of sound.
Keywords: Science-- Study and teaching (Primary) -- South Africa; Technology-- Study and teaching (Primary) -- South Africa; Ethnoscience; Storytelling; Folk dancing; Folk music; Sociocultural perspective; Argumentation theory